A personalized index to inform selection of a trauma-focused or non-trauma-focused treatment for PTSD. (July 2021) - Stirman, Shannon Wiltsey; Cohen, Zachary D.; Lunney, Carole A.; DeRubeis, Robert J.; Wiley, Joshua F.; Schnurr, Paula P.
Abstract: PTSD treatment guidelines recommend several treatments with extensive empirical support, including Prolonged Exposure (PE), a trauma-focused treatment and Present-Centered Therapy (PCT), a non-trauma-focused therapy. Research to inform treatment selection has yielded inconsistent findings with single prognostic variables that are difficult to integrate into clinical decision-making. We examined whether a combination of prognostic factors can predict different benefits in a trauma-focused vs. a non-trauma-focused psychotherapy. We applied a multi-method variable selection procedure and developed a prognostic index (PI) with a sample of 267 female veterans and active-duty service members (mean age 45; SD = 9.37; 53% White) with current PTSD who began treatment in a randomized clinical trial comparing PE and PCT. We conducted linear regressions predicting outcomes (Clinician-Administered PTSD Scale score) with treatment condition, the PI, and the interaction between the PI and treatment condition. The interaction between treatment type and PI moderated treatment response, moderated post-treatment symptom severity, b = 0.30, SE b = 0.15 [95% CI: 0.01, 0.60], p = .049. For the 64% of participants with the best prognoses, PE resulted in better post-treatment outcomes; for the remainder, there was no difference. Use of a PI may lead to optimized patient outcomes and greater confidence when selecting trauma-focused treatments. Highlights: A prognostic index was generated for each patient enrolled in PCT or PE for PTSD. PE resulted in better patient outcomes than PCT for patients in the top 63rd percentile for best prognoses. For those with worse prognoses, outcomes did not differ by treatment.